Attitudes and beliefs regarding complementary and alternative medicine in a diverse gynecologic oncology patient population - Miller, Emily A.; Beaumont, Shanice; Zhou, Zhen Ni; Brewer, Jesse T.; Thomas, Charlene; Chapman-Davis, Eloise; Cantillo, Evelyn; Holcomb, Kevin; Pua, Tara; Frey, Melissa K. (Gynecologic oncology reports, 2023)
•Complementary and alternative medicine use among diverse gynecologic oncology patients is less common than expected.•Race and ethnicity influence perceived benefits and barriers to complementary and alternative medicine use.•Higher income patients have fewer barriers to complementary and alternative medicine use.•Understanding attitudes and beliefs about complementary and alternative medicine promotes patient-centered care. To measure prevalence of complementary and alternative medicine (CAM) use in a diverse gynecologic oncology patient population and evaluate how attitudes and beliefs regarding CAM relate to demographic factors. A validated Attitudes and Beliefs about Complementary and Alternative Medicine (ABCAM) survey was distributed to patients with gynecologic malignancy. Results were evaluated using Pearson's Chi-squared and Fisher's exact tests for categorical variables and Wilcoxon ranks sum and Kruskal-Wallace tests for non-normally distributed variables. One-hundred thirty patients completed the ABCAM survey. Self-reported race and ethnicity included Asian or Pacific Islander (n = 54; 42%), Hispanic/Latino (n = 23; 18%), White (n = 21; 16%), Black or African American (n = 20; 15%), American Indian/Alaska Native (n = 8; 6.2%) and Other (n = 4; 3.1%). Twenty-four respondents (18%) reported use of CAM. There was a significant difference in expected benefits to CAM between respondents of different races/ethnicities (p < 0.001). Black and Asian respondents reported greater expected benefit to CAM. Hispanic/Latino, American Indian/Alaskan Native, and White respondents reported fewer expected benefits. A significant association was found between perceived barriers to CAM and race/ethnicity (p 0.043), with Asian, Hispanic/Latino and White respondents perceiving more barriers while Black and American Indian/Alaskan Natives reported perceiving fewer barriers to CAM. Respondents with incomes greater than $100,000 reported fewer barriers to CAM. Use of CAM among gynecologic oncology patients is lower than previously thought. Income, race, and ethnicity inform patient engagement with CAM and can be used to better tailor the provision of evidence-based CAM interventions to benefit a greater number of gynecologic cancer patients.